The heterogeneity of crowdfunders - Lin, Yan (2017)
Crowdfunding refers to the practice by which funding resources are pooled by people, usually via the Internet, to support efforts initiated by others. Prior research tends to treat crowdfunders on a particular platform as a homogeneous group, adopting a certain strategy or behavior. However, the Internet allows crowdfunding to reach out to a much wider audience than traditional fundraising channels. The possibility that different crowdfunders may exhibit different behaviors and funding strategies has important implications for theory building and practice. This dissertation unpacks the complexities of the crowdfunder community based on the premise that crowdfunders on the same platform are a heterogeneous rather than a homogeneous group. In the first essay, I draw upon the opinion leadership literature and begin to explore the complexities of crowdfunder community by identifying different archetypes of crowdfunders funding technology projects in Kickstarter, one of the world’s most prominent reward-based crowdfunding platforms. I identified five distinct types of crowdfunders: the Vocal Actives, the Silent Actives, the Focused Enthusiasts, the Trend Followers, and the Star Seekers. Based on the understanding that crowdfunders are heterogeneous, the second essay examines the effects of one of the most visible and important dimensions of crowdfunder heterogeneity – crowdfunder experience. Drawing upon the Elaboration Likelihood Model (ELM), I investigate two broad sets of information a potential crowdfunder might rely on to overcome the information asymmetry problem: the signals embedded in the project content and the social information derived from observing other crowdfunders’ decisions and comments. I show that a crowdfunder’s ability to process information increases with his/her experience. Experienced crowdfunders are more likely to process information via the central route and rely more on the content of information. In contrast, inexperienced crowdfunders are more likely to process information via the peripheral route and rely more on cues. Overall, I show that crowdfunders on the same platform adopt different strategies and behaviors, and discuss how this informs theory building and practice.